2014
DOI: 10.1128/jvi.01908-14
|View full text |Cite
|
Sign up to set email alerts
|

The Exonuclease Domain of Lassa Virus Nucleoprotein Is Involved in Antigen-Presenting-Cell-Mediated NK Cell Responses

Abstract: Lassa virus is an Old World

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Our findings are supported by recent studies with recombinant LASV carrying the NP catalytic double mutations (D389T/G392A and D389A/G392A), which lose the ability to suppress the type I IFN-induction pathway in dendritic cells or macrophages, which are thought to be primary target cells for virus infection [ 6 , 7 ]. The inability of the LASV NP catalytic mutants to suppress type I IFNs results in upregulated expression levels of major histocompatibility complex (MHC) class I gene pathways as well as important macrophage-derived cytokines that activate natural killer (NK) cells to participate in the direct killing of the infected cells.…”
supporting
confidence: 85%
“…Our findings are supported by recent studies with recombinant LASV carrying the NP catalytic double mutations (D389T/G392A and D389A/G392A), which lose the ability to suppress the type I IFN-induction pathway in dendritic cells or macrophages, which are thought to be primary target cells for virus infection [ 6 , 7 ]. The inability of the LASV NP catalytic mutants to suppress type I IFNs results in upregulated expression levels of major histocompatibility complex (MHC) class I gene pathways as well as important macrophage-derived cytokines that activate natural killer (NK) cells to participate in the direct killing of the infected cells.…”
supporting
confidence: 85%
“…The Lassa virus nucleoprotein (NP) has the capacity to block IFN induction which involves, at least in part, NP 3’-5’ exonuclease activity [85-87]. Lassa virus NP is also involved in the inhibition of antigen-presenting cell (DC and macrophage)-mediated NK cell responses [88]. It has also been shown that the LASV Z protein can inhibit RIG-I and Melanoma Differentiation-Associated protein 5 (MDA5) [89,90].…”
Section: Similarities Of Other Vhfs To Ebola Virusmentioning
confidence: 99%
“…Interestingly, outside the order Nidovirales, the only other known RNA virusencoded 3=-to-5= exoribonucleases are found in the Arenaviridae family of viruses. Lassa fever virus nucleoprotein ExoN is not thought to participate in fidelity regulation; rather, it participates in immune evasion by degrading dsRNA and thereby prevents antigen-presenting cell-mediated NK cell activation (18)(19)(20). Recently, in the Alphacoronavirus transmissible gastroenteritis virus (TGEV), a mutation in the nsp14 ExoN zinc finger was shown to generate lower levels of dsRNA than wild-type (WT) TGEV.…”
mentioning
confidence: 99%